Primitive herbaceous lychophytes record at the Río Seco de los Castaños Formation, San Rafael Block, Mendoza province, Argentina - Morel, Eduardo Manuel (2007)
The San Rafael or Sierra Pintada Block is situated at the central-western of the Mendoza province and shows diverse igneous, metamorphic and sedimentary units of Mesoproterozoic to Paleozoic age, known generally as ‘pre-Carboniferous’ due to they are clearly separated by a regional unconformity. One of these units is the Río Seco de los Castaños Formation (González Díaz, 1972; 1981) that was initially considered as a part of the La Horqueta low-grade methamorphic ‘Serie’ (Dessanti, 1956) and was later distinguished because of its marine sedimentary characteristics and assigned to the Devonian because of a coral record (Pleurodyctium) carried out by Di Persia (1972). In other contributions, Nuñez (1976) and Criado Roque and Ibañez (1979) have described several sedimentary and structural features of this unit. Later works (Poiré et al., 2002 and Manassero et al., 2005, for example), have recognized trace fossils associations in the Agua del Blanco locality, improving the interpretation of different sub-environments of deposition within a wide siliciclastic marine platform with gravity flow deposits developed in deeper sectors.